Age-Associated Changes in Adverse Events Arising From Anti-PD-(L)1 Therapy - Huang, Xinyi; Tian, Tiantian; Zhang, Yan; Zhou, Shengjian; Hu, Pingping; Zhang, Jiandong (Frontiers in Oncology, 2021)
Background: Immune-related adverse events (irAEs) may complicate the immune checkpoint inhibition (ICI) therapy. The effect of age on these irAEs is not elucidated. The aim of the study was to compare the occurrence of irAEs in different age groups. Methods: Patients with lung cancer receiving anti-programmed death-1/ligand-1 (PD-1/-L1) were selected from the US Food and Drug Administration Adverse Event Reporting System (FAERS) database. Immune cell infiltration dataset was obtained from TIMER 2.0 web server. The patients were stratified for age as follows: <65 year-old (young patients, YP), 65-75 year-old (middle aged patients, MP), ≥75 year-old (old patients, OP). The severity of irAEs was compared using logistic binary regression model. The distribution differences of immune cell infiltration were estimated using non-parametric tests. Results: Of all the 17006 patients treated by anti-PD-1/-L1, 7355 were <65 (YP), 6706 were 65-75 (MP), and 2945 were ≥75 (OP). In general, we analyzed a total of 16 irAEs in this article and found that pulmonary toxicity and radiation pneumonitis were more frequent in OP (OP vs. YP: OR=1.45, 95%CI: 1.28-1.64 and OR=1.94, 95% CI, 1.46-2.58, respectively) and MP (MP vs. YP: OR=1.38, 95%CI: 1.24-1.52 and OR=1.74, 95%CI: 1.37-2.21, respectively), but hepatitis was less frequent in OP (OP vs. YP: OR=0.56, 95%CI: 0.32-0.97) and MP (MP vs. YP: OR=0.57, 95%CI: 0.38-0.85). Further analysis demonstrated that older patients showed less B cell, CD8+ T cell and myeloid dendritic cell infiltration than younger patients. Conclusions: Elderly patients exhibited higher incidences of pulmonary toxicity and radiation pneumonitis, while hepatitis was found at low incidence. Therefore, clinicians should carefully monitor comorbidities in elderly patients.